Turnover Intention ditinjau dari Work Family Enrichment pada Karyawan Tango Musik di Medan - Sri Hartini; Grazia Tanzil (Jurnal Spiritual Healing, 2022)
This study aims to determine the relationship between work family enrichment with turnover intention. The hypothesis of this study states that there is a negative relationship between work family enrichment and turnover intention, assuming that the higher the work family enrichment, the lower the turnover intention and conversely the lower the work family enrichment, the higher the turnover intention. The subjects of this study were 105 officer of Tango Musik Medan. Data were obtained from a scale to measure the work family enrichment and turnover intention. Calculations were performed to test the requirements analysis (assumption) that consisted of a test for normality and linearity. The data were analyzed by Product Moment Correlation with SPSS 17 for Windows. The results of data analysis showed that the correlation coefficient was -.622 with a significance value of 0.000 (p <0.05). It showed that there is a negative relationship between work family enrichment and turnover intention. The results of this study indicate that the contributions made by the variable of work family enrichment on turnover intention was 38 percent, while the remaining 62 percent was influenced by other factors not examined. From these results it is concluded that the hypothesis stating that there is a negative relationship between the work family enrichment and turnover intention is acceptable.